Stick-slip statistics for two fractal surfaces: a model for earthquakes - Chakrabarti, B; Stinchcombe, R (1999)
Following the observations of the self-similarity in various length scales in the roughness of the fractured solid surfaces, we propose here a new model for the earthquake. We demonstrate rigorously that the contact area distribution between two fractal surfaces follows a unique power law. This is then utilised to show that the elastic energy releases for slips between two rough fractal surfaces indeed follow a Guttenberg-Richter like power law. (C) 1999 Elsevier Science B.V. All rights reserved.